Sand chronicles. Vol. 06 - Ashihara, Hinako (Shojo beat manga, 2009)
"Ann and Daigo begin dating other people. But can anyone take the place of her first love in Ann's heart? Then, Ann learns a surprising secret about her father's romantic life!"--Page 4 of cover.